Evaluation of the effectiveness of the human-baited double net traps and BG traps compared with the human landing catches for collecting outdoor Aedes albopictus in China - Yuyan Wu; Juan Hou; Qinmei Liu; Jinna Wang; Tianqi Li; Mingyu Luo; Zhenyu Gong (BMC, 2023)
Abstract Dengue fever is one of the biggest threats to public health in China, causing huge disease burden and economic loss. Aedes-mosquito surveillance could be a cornerstone for predicting the risk of Aedes-borne diseases and evaluating the effect of vector management during diseases outbreaks. The human landing catch (HLC) method is regarded as the "gold standard" for catching Aedes mosquitoes, but it potentially exposes field professionals to vectors of known or unknown pathogens. Human-baited double net (HDN) was recommended to replace HLC for emergency monitoring in China when Aedes-borne diseases break out, but it had been reported with low efficiency for capturing Aedes mosquitoes. In this study, we compared HLC with HDN and BG traps for field Aedes albopictus monitoring, with the aim of evaluating the effectiveness of HDN replacing HLC and finding an effective and safe alternative to the HLC for monitoring Aedes albopictus. Six sites in Hangzhou, Shaoxing, and Yiwu, Zhejiang Province, China, were chosen to conduct outdoor HLC, HDN, and BG trap catches from June to October 2021. The tests were performed 3 h apart: 8:30-9:30 AM, 16:30-17:30 PM, and 17:30-18:30 PM. A total of 2330 adult mosquitoes were collected, and Aedes albopictus was the most abundant species in all three catches with 848(98.95%), 559(97.39%) and 867 (96.44%) caught in HLC, HDN and BG traps respectively. Compared to HLC, HDN collected significantly less Ae. albopictus and Ae. albopictus females per trapping period (P < 0.001, P < 0.001), whereas no statistical differences were found between the HLC and BG trap (P = 0.970, P > 0.05). Statistically significant positive spatial correlations for Ae. albopictus sampling was found between HLC and HDN traps (r = 0.543, P < 0.001) and HLC and BG traps (r = 0.658, P < 0.001). In conclusion, both the BG trap and HDN have a significant positive spatial correlation with HLC, making them safer alternatives to HLC for Ae. albopictus monitoring in China. However, with better a sampling efficiency, being less labor intensive, and no human-baited attraction bias, the BG trap could be a better choice than the HDN trap.